ESTIMASI EKIVALENSI MOBIL PENUMPANG BERDASAR DATA KECEPATAN PADA JALAN TOL (ESTIMATION OF PASSENGER CAR EQUIVALENCE BASED ON SPEED FOR TOLL ROADS) - Tri Basuki Joewono; Kiagoes Moehammad H.N. Nugraha; Zelina Alviana (Direktorat Bina Teknik Jalan dan Jembatan, 2018)
Several studies have been completed to adjust the value of PCE to be more in line with the existing changes in field. This study aims to analyze the speed distribution of two toll road segments and use it to estimate the PCE. This study was conducted using data of flow and speed for inter and intra city, namely Jakarta-Cikampek and Jakarta Outer Ringroad. The result of analysis shows that the speed in these two toll roads followed the normal distribution and the PCE’s values of intra city are greater than inter city. Result of comparison shows that the pce’s values based on speed are smaller than those in MKJI 1997. Keywords: pce, speed, toll roads, intra city, inter city